The Mastery of Diction, Speaking Interest, and Public Speaking Skill: A Correlational Study at Vocational High School Students - Yeyen Fatmala; Supriyono Supriyono; Joko Sutrisno AB; Aksendro Maximilian (IJLHE: International Journal of Language, Humanities, and Education, 2020)
This study aims to describe the relationship between the mastery of diction, speaking interest and public speaking skill in the context of the students of the Vocational High School in Indonesia. The subjects of this study were the students of SMK Swadhipa 2 Natar, South Lampung, Indonesia. Researchers used the correlational method. The instruments used to collect research data were questionnaire and test. The hypothesis testing of this study was conducted using the product-moment correlation and multiple correlation formula. The results of the statistical test analysis showed that there was a significant correlation between the mastery of diction and the public speaking skill. The correlation between the students’ speaking interest and public speaking skill was also proven significant. Moreover, this research also found that there was a significant relationship between the mastery of diction, the speaking interest, and the public speaking skill of Vocational High School students.